An investigation into anti-proliferative effects of microRNAs encoded by the miR-106a-363 cluster on human carcinoma cells and keratinocytes using microarray profiling of miRNA transcriptomes - Khuu, Cuong; Jevnaker, Anne-Marthe; Bryne, Magne; Osmundsen, Harald (Frontiers in Genetics, 2014)
Transfection of human oral squamous carcinoma cells (clone E10) with mimics for unexpressed miR-20b or miR-363-5p, encoded by the miR-106a-363 cluster (miR-20b, miR-106a, miR-363-3p or miR-363-5p), caused 40-50% decrease in proliferation. Transfection with mimics for miR-18a or miR-92a, encoded by the miR-17-92 cluster (all members being expressed in E10 cells), had no effect on proliferation. In contrast, mimic for the sibling miRNA-19a yielded about 20 % inhibition of proliferation. To investigate miRNA involvement profiling of miRNA transcriptomes were carried out using deoxyoligonucleotide microarrays. In transfectants for miR-19a, or miR-20b or miR-363-5p most differentially expressed miRNAs exhibited decreased expression, including some miRNAs encoded in paralogous miR-17-92 - or miR-106b-25 cluster. Only in cells transfected with miR-19a mimic significantly increased expression of miR-20b observed - about 50-fold as judged by qRT-PCR. Further studies using qRT-PCR showed that transfection of E10 cells with mimic for miRNAs encoded by miR-17-92 -, or miR-106a-363 – or the miR-106b-25 cluster confirmed selective effect on expression on sibling miRNAs. We conclude that high levels of miRNAs encoded by the miR-106a-363 cluster may contribute to inhibition of proliferation by decreasing expression of several sibling miRNAs encoded by miR-17-92 or by the miR-106b-25 cluster. The inhibition of proliferation observed in miR-19a-mimic transfectants is likely caused by the miR-19a-dependent increase in the levels of miR-20b and miR-106a. Bioinformatic analysis of differentially expressed miRNAs from miR-106a, miR-20b and miR-363-5p transfectants, but not miR-92a transfectants, yielded significant associations to “Cellular Growth and Proliferation” and “Cell Cycle”. Western blotting results showed that levels of affected proteins to differ between transfectants, suggesting that different anti-proliferative mechanisms may operate in these transfectants.